Timely extraction of the first permanent molars severely affected in mixed dentition. - Javiera Scheu; Cecilia Cerda; Víctor Rojas (Universidad de Concepción., 2019)
The aim of this study was to establish a guide for general dentists that allow identifying the ideal moment to extract the first permanent molars with poor prognosis, in the hope of obtaining a spontaneous closure of space, regarding that the first permanent molar is more susceptible to develop dental caries in children due to its early eruption in the oral cavity and molar incisor hypomineralization affects them the most. Methods: we proceed to search for the articles in databases PUBMED and SciELO, selected articles published from 1998 a 2018 were analyzed based on inclusion and exclusion criteria. Conclusion: Our review suggests that a full evaluation of the compromised first permanent molar should be performed before planning an extraction. It can be concluded that the ideal stage to extract a first permanent molar with bad prognosis is in the Demirjian stage E or D evaluated with radiographs, which is generated at a chronological age of 8 to 10.5 years, ideally in the presence of third molars.